2010
DOI: 10.1109/tnsre.2010.2052471
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Stimulation of the Rectus Femoris During Pre-swing Diminishes Hip and Knee Flexion During the Swing Phase of Normal Gait

Abstract: Individuals who have suffered cerebral insults often exhibit stiff-knee gait, a condition characterized by reduced knee flexion during swing. We investigated the effect that an increment in normal rectus femoris (RF) activity can have on hip and knee joint angles during swing, as a first step to determining this muscle's involvement in stiff-knee gait. For this, we developed a protocol that electrically stimulated the RF during pre-swing or after toe-off in randomly selected strides of treadmill walking, consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 40 publications
0
25
0
Order By: Relevance
“…Induced accelerations characterize the instantaneous capacity of a muscle to generate accelerations, which is dependent on the current posture but independent of other muscles. In contrast, our forward dynamics simulations measure changes in joint position, which evolve over time and therefore include the effect of biomechanical and neural interactions (Anderson et al, 2004; Hernandez et al, 2010). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Induced accelerations characterize the instantaneous capacity of a muscle to generate accelerations, which is dependent on the current posture but independent of other muscles. In contrast, our forward dynamics simulations measure changes in joint position, which evolve over time and therefore include the effect of biomechanical and neural interactions (Anderson et al, 2004; Hernandez et al, 2010). …”
Section: Discussionmentioning
confidence: 99%
“…During post-processing, EMG activities during cycles before and during stimulation were rectified. To evaluate spill-over, we quantified induced muscle activities by integrating rectified EMG between stimulus pulses, after a brief time period to allow for the direct stimulation pulse effects to dissipate on each electrode (Hernandez et al, 2010) (Fig. 2).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, several studies have attempted to validate scaled length–tension relationships for whole muscles, 68 to simulate the three-dimensional geometry of muscles during contraction, 7 and to qualitatively confirm the actions of select muscles predicted by simulations. 27 However, the accuracy with which traditional, Hill-type models predict muscle forces during in vivo activities remains untested.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, RF tends to decrease the peak knee flexion velocity (Goldberg et al 2004; Goldberg et al 2006) and over activity during region 4 and swing is often implicated in stiff knee gait (Goldberg et al 2004). Additionally, Hernandez et al (2010) in their electrical stimulation study reported that RF stimulation before the toe-off largely reduced the peak knee flexion during swing as opposed to the stimulation during the swing phase. Reduced propulsion due to increased activity of RF in the non-paretic leg is further supported by reduced propulsive impulse generation during region 4 of stance phase, specifically in moderate and fast speed groups.…”
Section: Discussionmentioning
confidence: 98%